2023
DOI: 10.7150/ijms.79889
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Unstable Plaque in Acute Coronary Syndrome: A Systematic Review of The Role of Matrix Metalloproteinases

Abstract: Smoking is a risk factor of acute coronary syndrome (ACS) that could increase matrix metalloproteinases (MMPs) levels, leading to unstable coronary artery plaque. The current review aimed to identify the relationship between smoking and MMPs in patients with ACS. Literature search was conducted from inception until March 2022 in three online databases. Risk of bias was assessed using the Newcastle-Ottawa Scale. A meta-analysis was performed, and the odds ratio (OR) together with its 95% confidence interval (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 64 publications
0
2
0
1
Order By: Relevance
“…Conforme observado em outros estudos, a hipertensão arterial sistêmica juntamente com dislipidemia foram as comorbidades mais frequentes na amostra (Khalil et al, 2021;Paudel et al, 2019). A proporção de tabagistas em metade desta população mostrou-se mais alta do que a normalmente encontrada nos estudos, sendo um fator de risco importante para DAC, muito associado à instabilidade da placa aterosclerótica (Aminuddin et al, 2023;Soeiro et al, 2018;Kumar Jha et al, 2017).…”
Section: Discussionunclassified
“…Conforme observado em outros estudos, a hipertensão arterial sistêmica juntamente com dislipidemia foram as comorbidades mais frequentes na amostra (Khalil et al, 2021;Paudel et al, 2019). A proporção de tabagistas em metade desta população mostrou-se mais alta do que a normalmente encontrada nos estudos, sendo um fator de risco importante para DAC, muito associado à instabilidade da placa aterosclerótica (Aminuddin et al, 2023;Soeiro et al, 2018;Kumar Jha et al, 2017).…”
Section: Discussionunclassified
“…Dyslipidemia is common in ACS patients and requires effective management for secondary prevention, yet many fail to achieve optimal lipid levels despite treatment efforts. [8] Smoking is a substantial risk factor for ACS [9] . Over a 4-year period, continuing to smoke after developing ACS was linked to a 78% increased relative risk of death.…”
Section: Introductionmentioning
confidence: 99%
“…Even after quitting smoking, the increased risk of coronary heart disease can persist for up to 20 years [2]. A large body of evidence has indicated that smoking accelerates atherosclerosis and vulnerable plaque formation [3][4][5]. Over the past few decades, efforts have been made to reduce the harmful effects of smoking by lowering tar yield, the primary toxic component in cigarettes [6].…”
Section: Introductionmentioning
confidence: 99%